Z Tracji do Grecji. Sabeth z powieści Maxa Frischa i jej związek z Wergiliuszową Eurydyką - Arndt, Aleksandra (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article presents the possible influence of Virgil’s epyllion in his Georgics on the shaping of Sabeth, one of the heroines of Max Frisch’s novel Homo Faber.